2021
DOI: 10.1097/ico.0000000000002655
|View full text |Cite
|
Sign up to set email alerts
|

Exacerbation of Granular Corneal Dystrophy Type 2 After Small Incision Lenticule Extraction

Abstract: Purpose: To report the outcome of unilateral small incision lenticule extraction (SMILE) in a patient with granular corneal dystrophy type 2 (GCD2). Methods: Slit-lamp photography and Fourier domain optical coherence tomography were used to document the clinical course and appearance of the corneas in a patient with genetically determined GCD2 who underwent unilateral SMILE in the right eye. Results: Slit-lamp examination of a 23-year-old wom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…They identified elongated basal epithelial cells, epithelial hyperplasia, epithelial basement membrane thickening and undulations, and Bowman layer undulations on the flap surface; they also observed activated keratocytes and eosinophilic deposits in the lamellar wound. Kwak et al 10 reported a patient with GCD2 with exacerbated corneal deposits after SMILE. They observed 2 distinct types of deposits, one at the interface and the other immediately beneath the Bowman layer or at the subepithelium.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…They identified elongated basal epithelial cells, epithelial hyperplasia, epithelial basement membrane thickening and undulations, and Bowman layer undulations on the flap surface; they also observed activated keratocytes and eosinophilic deposits in the lamellar wound. Kwak et al 10 reported a patient with GCD2 with exacerbated corneal deposits after SMILE. They observed 2 distinct types of deposits, one at the interface and the other immediately beneath the Bowman layer or at the subepithelium.…”
Section: Discussionmentioning
confidence: 99%
“…These deposits were observed over a decade after the patients underwent keratorefractive surgery, resembling previously documented reports. 1,2,5,10 All 4 patients denied having a family history of ocular diseases and reported an uneventful postoperative course. In most corneal dystrophies, the deposits are centrally located in the cornea.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As the epithelium, which is not connected to the limbal epithelium directly, there would be limit for the continuation of the growth. If the debris are the ones with exacerbated granular corneal dystrophy type 2 after SMILE, the number and size of the deposits would increase with time 1 . In addition, the deposits would be located more at the central cornea.…”
Section: Eung Kweon Kim MD Phdmentioning
confidence: 99%